The ethical aspects of halal certification of medical devices in Malaysia - Zarmani, N.F.; Ramli, M.A.; Shaikh Mohd Salleh, S.M.S. (2014)
The medical devices industry is one of the fastest growing sectors of healthcare industry with a large market, a wide variety of products and growing applications. In Malaysia, this industry is a major contributor to the economy and government initiatives support its growth to position Malaysia as a medical device manufacturing hub in the Asia- Pacific region. There are more than 180 manufacturers of medical devices in Malaysia involved in the production of sophisticated devices such as orthopedic products, surgical instruments and dialysis machines. Local companies are moving towards complying with internationally recognized quality standards such as ISO 13485 as an attempt to penetrate the global market. However, there is a religious need to provide medical devices that are certified halal in order to cater to the needs of Muslim consumers who make up 64.3% of the Malaysian population. It is an advantage that Malaysia halal certification industry is well-developed and recognized as a model all around the world. Malaysia shows a strong industrial manufacturing potential for a wide range of halal products. The availability of supporting industries thus provides Malaysia with the ideal conditions to develop into a medical device hub in Asia as well as to establish a global acceptance model for halal medical devices. This paper will discuss the ethical aspects of developing halal medical devices for the needs of Muslims in Malaysia and other Islamic nations.